2013
DOI: 10.1002/ptr.5019
|View full text |Cite
|
Sign up to set email alerts
|

Pycnogenol® in Chronic Venous Insufficiency and Related Venous Disorders

Abstract: The present review provides an update of the biological profile of Pycnogenol in the light of its use in the treatment of chronic venous insufficiency (CVI) and related venous disorders such as deep vein thrombosis (DVT), post-thrombotic syndrome, long haul air-travel-related leg oedema, venous ulcers and acute haemorrhoids. Pycnogenol is a French maritime pine bark extract produced from the outer bark of Pinus pinaster Ait. subsp. atlantica. Its strong antioxidant, anti-inflammatory and vasodilator activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 62 publications
(80 reference statements)
0
33
0
1
Order By: Relevance
“…Combined PYC and compression decreased ankle swelling, resting flux, transcutaneous oxygen pressure, and other clinical symptoms (Cesarone et al, 2010). Clinical studies have shown that PYC can reduce leg edema in chronic venous insufficiency, reduce the incidence of deep vein thrombosis during long-haul flights, and enhance the healing of venous ulcers and hemorrhoidal episodes by topical application and/or oral administration (Gulati, 2014).…”
Section: Organ Protective Effects Of Pbe Cardiovascular Protectionmentioning
confidence: 99%
“…Combined PYC and compression decreased ankle swelling, resting flux, transcutaneous oxygen pressure, and other clinical symptoms (Cesarone et al, 2010). Clinical studies have shown that PYC can reduce leg edema in chronic venous insufficiency, reduce the incidence of deep vein thrombosis during long-haul flights, and enhance the healing of venous ulcers and hemorrhoidal episodes by topical application and/or oral administration (Gulati, 2014).…”
Section: Organ Protective Effects Of Pbe Cardiovascular Protectionmentioning
confidence: 99%
“…Son çalışmalar, relaksinin alt ekstremitelerde, venöz kapaklar üzerinde artmış basınca katkıda bulunan potansiyel bir vazo- 38 Pycnogenol için-deki aktif prosiyanidinlerin, kılcal geçirgenliği azalttığı, mikrosirkülasyonu ve vasküler endotelyal fonksiyonunu geliştirdiği gösterilmiştir. 1,39,40 Prostaglandin E1 (PGE1) beyaz hücre aktivasyonunun azaltılması, trombosit agregasyonu inhibisyonu, küçük damar genişlemesi ve damar çeperinde kolesterol seviyelerinin azaltılması dâhil olmak üzere mikrosirkülasyon üzerinde bir dizi derin etkiye sahiptir. 41 …”
Section: Kroni̇k Venöz Yetmezli̇kte Ri̇sk Faktörleri̇unclassified
“…These include (i) antioxidant and free radical scavenging activity (Blazso et al , ; Nelson et al , , Puruhito, , Rong et al , , Wei et al , ); (ii) antioxidant activity resulting in sparing vitamin C and recycling of vitamin E (Rimbach et al , ); (iii) inhibition of lipid peroxidation (Kim et al , ); (iv) protection of nerve cells against β‐amyloid/or glutamate‐induced toxicity (Peng et al , ); (v) protection against potassium dichromate‐induced nephrotoxicity (Parveen et al , ); (vi) reducing hyperglycaemia‐induced oxidative stress in diabetic rats (Parveen et al , ); (vii) protection against ischemia‐reperfusion‐induced oxidative stress and causing kidney damage in rats (Ozer Sehirli et al , ); (viii) erythrocyte protection in G6PD deficiency (Kohama et al , ); (ix) hepato‐protective effect (Yang et al , ); (x) stimulation of the anti‐oxidative defence system (Taner et al , , Taner et al , ); (xi) anti‐erythema, anti‐oedema and antiinflammatory effects (Blazso et al , , Blazso et al , , Rohdewald, , Saliou et al , ); (xii) inhibition of pro‐inflammatory cytokines (Cho et al , ); (xiii) inhibition of matrix metallo‐proteases (Grimm et al , ); (ixv) inhibition of histamine release from mast cells (Nelson et al , ) and (xv) wound healing effects (Belcaro et al , , Blazso et al , ). These have been reviewed and discussed earlier (Gulati, , Gulati, ) so the main focus of this review is on the clinical research findings in metabolic syndrome and related conditions.…”
Section: Pharmacological Profile Of Pycnogenolmentioning
confidence: 99%
“…Kidney‐protective effects have been shown with Pycnogenol in hypertensive subjects (Cesarone et al , , ). Clinical research data on Pycnogenol have earlier been reviewed for different indications, like chronic venous insufficiency, cardiovascular health, and arthritis (Blumenthal, , Gulati, , Gulati, , Gulati, , Gulati, , Nuzum et al , ; Oliff, , Rohdewald, ). The present review provides an update of the multifaceted biological profile of Pycnogenol in metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%